The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/catal8120569
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Stimuli-Responsive Heterogeneous Catalysis

Abstract: Heterogeneous catalytic systems based on the use of stimuli-responsive materials can be switched from an "on" active state to an "off" inactive state, which contributes to endowing the catalysts with unique functional properties, such as adaptability, recyclability and precise spatial and temporal control on different types of chemical reactions. All these properties constitute a step toward the development of nature-inspired catalytic systems. Even if this is a niche area in the field of catalysis, it is poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…Altering the materials solubility results in controlled activation or deactivation of the catalyst by controlling access of reagents to the catalytic sites. [5] In biological systems,f unctions or activities can be enabled or disabled by triggers,w hich lead to structural changes in conformation and, therefore,a ctivity control. For artificial materials,m ultiple stimuli have previously been reported that can be utilized to modify the physical properties of classical polymers most notably change by light, [6] pH value, [7] and temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Altering the materials solubility results in controlled activation or deactivation of the catalyst by controlling access of reagents to the catalytic sites. [5] In biological systems,f unctions or activities can be enabled or disabled by triggers,w hich lead to structural changes in conformation and, therefore,a ctivity control. For artificial materials,m ultiple stimuli have previously been reported that can be utilized to modify the physical properties of classical polymers most notably change by light, [6] pH value, [7] and temperature.…”
mentioning
confidence: 99%
“…Dual-responsive thermo-and light-sensitive polymer nanogels were designed so that photocatalysis could be quenched through changes in temperature.The contraction of the photocatalytic sites within the polymer gel network is demonstrated in Scheme 1, in which the gel network becomes insoluble and precipitates upon an increase in temperature, which shields the photocatalytic units and retards partitioning of the reagents into the network. [5] Furthermore,t he condensation of the nanogel network upon temperature elevation may limit light penetration into the gel network. A decrease in temperature to ambient conditions results in ar ewetting of the gel network increasing the transfer of reagents from the continuous phase to the active regions.This reversible behaviour of the photocatalytic nanogel enables photocatalysis to be turned on or off depending on temperature in amanner analogous to enzymatic functions within the body.…”
mentioning
confidence: 99%
“…[4] Them ain challenges within these photocatalytic systems is maintaining efficient catalysis whilst producing amaterial that can be easily recovered. [5] In biological systems,f unctions or activities can be enabled or disabled by triggers,w hich lead to structural changes in conformation and, therefore,a ctivity control. Altering the materials solubility results in controlled activation or deactivation of the catalyst by controlling access of reagents to the catalytic sites.…”
mentioning
confidence: 99%
“…[5] Furthermore,t he condensation of the nanogel network upon temperature elevation may limit light penetration into the gel network. [5] Furthermore,t he condensation of the nanogel network upon temperature elevation may limit light penetration into the gel network.…”
mentioning
confidence: 99%
“…Finally, the CPG is obtained after time consuming acidic and alkaline leaching. In addition, functionalizing Pd nanoparticles in next-generation matrix supports, such as pH-responsive polymers, is another feasible way to obtain high-performance Pd-based catalysts [25].…”
Section: Introductionmentioning
confidence: 99%